2007
DOI: 10.1634/stemcells.2006-0814
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Culture Technique for Human Embryonic Stem Cells Using Porous Membranes

Abstract: We have developed a novel culture technique for human embryonic stem cells (hESCs) using a porous membrane with feeder cells. The feeder cells were seeded and attached to the bottom of a porous membrane and, subsequently, hESCs were cultured on the top of the membrane. This porous membrane technique (PMT) allowed hESCs to be successfully cultured and to be effectively and efficiently separated from the feeder cell layer without enzyme treatment. hESCs being cultured by PMT were observed to interact with feeder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…Co-culture-iPSCs (CiPSCs) have the same characteristics, differentiation, expression of pluripotent markers, and morphology as embryonic stem cells (ESCs) grown in colonies in vitro. A previous study found that human ESCs and iPSCs can be propagated using this method (Kim et al, 2007;Abraham et al, 2010). In our study, we provide evidence that this culture system is convenient and simple to use in research concerning the reprogramming mechanism of stem cells in an in vitro environment.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Co-culture-iPSCs (CiPSCs) have the same characteristics, differentiation, expression of pluripotent markers, and morphology as embryonic stem cells (ESCs) grown in colonies in vitro. A previous study found that human ESCs and iPSCs can be propagated using this method (Kim et al, 2007;Abraham et al, 2010). In our study, we provide evidence that this culture system is convenient and simple to use in research concerning the reprogramming mechanism of stem cells in an in vitro environment.…”
Section: Introductionsupporting
confidence: 62%
“…Furthermore, C-iPSCs had the ability to form teratomas after injection into nude mice, and three germ layers formed within 30 days. This method conveniently allows for the easy separation of feeder cells without enzyme treatment from iPSCs midway through the process of induction (Kim et al, 2007). In addition, MEF cells can be used for feeder cells directly.…”
Section: Discussionmentioning
confidence: 99%
“…The PET membrane with 1 mm pore size was selected because it has been reported that only the 1 mm pore can effectively minimize the migration of mouse embryonic fibroblast feeder cells to zero during culture, while the 3 and 8 mm pores cannot. 18 This method of 3D culture is called the ''sandwich method'' in the rest of the article. Limbal epithelial cells in single-cell suspension were cultured for 14-21 days and collected before confluence.…”
Section: Standard and Sandwich Culture Methodsmentioning
confidence: 99%
“…Three different hESC lines were used in this study: SNUhES3 (Institute of Reproductive Medicine and Population, Medical Research Center, Seoul National University, Korea), 11 CHA3-hESC (Stem Cell Research Laboratory, CHA Stem Cell Institute, Pochon CHA University, Korea), 12 and H9 (Wisconsin Regional Primate Research Center, University of Wisconsin). Mitomycin-C-treated (Sigma, St. Louis, MO) SIM mouse embryo-derived thioguanine and ouabain resistant (STO) feeder system and mitomycin-C-treated mouse embryonic fibroblast feeder system were used for SNUhES3, CHA3-hESC, and H9, respectively, in 0.1% gelatin (Sigma)-coated tissue culture dishes at 378C and 5% CO 2 in an air atmosphere.…”
Section: Culture Of Hescsmentioning
confidence: 99%